2003
DOI: 10.1073/pnas.1534570100
|View full text |Cite
|
Sign up to set email alerts
|

Human cytomegalovirus UL83-coded pp65 virion protein inhibits antiviral gene expression in infected cells

Abstract: The initial interaction of human cytomegalovirus with fibroblasts triggers, and then partially blocks, an innate immune response pathway that leads to the induction of IFN-responsive genes and proinflammatory chemokines. Infection of fibroblasts with human cytomegalovirus inhibited their ability to respond to exogenous IFN. Consistent with the observation that the block did not depend on de novo viral protein synthesis, ectopic expression of the viral UL83-coded pp65, an abundant virion protein, inhibited IFN … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
174
5
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(190 citation statements)
references
References 36 publications
8
174
5
3
Order By: Relevance
“…4) and downregulates the basal NF-kB activity. The HCMV tegument protein pp65 (pUL83) was reported to counteract innate antiviral defence, including NF-kB activity (Browne & Shenk, 2003) and IRF3 activation (Abate et al, 2004). In addition, an indirect effect on inhibition of IFN-b expression by deletion of the UL83-ORF was described previously (Taylor & Bresnahan, 2006b) DCs respond to MCMV with a strong type I IFN production (Krug et al, 2004;Tabeta et al, 2004;Delale et al, 2005;Andoniou et al, 2005).…”
Section: T K Le and Othersmentioning
confidence: 99%
See 1 more Smart Citation
“…4) and downregulates the basal NF-kB activity. The HCMV tegument protein pp65 (pUL83) was reported to counteract innate antiviral defence, including NF-kB activity (Browne & Shenk, 2003) and IRF3 activation (Abate et al, 2004). In addition, an indirect effect on inhibition of IFN-b expression by deletion of the UL83-ORF was described previously (Taylor & Bresnahan, 2006b) DCs respond to MCMV with a strong type I IFN production (Krug et al, 2004;Tabeta et al, 2004;Delale et al, 2005;Andoniou et al, 2005).…”
Section: T K Le and Othersmentioning
confidence: 99%
“…protein kinase R and RNaseL (Child et al, 2004(Child et al, , 2006Valchanova et al, 2006). A HCMV mutant lacking UL83 was found to be deficient in inhibition of IFNb gene expression, leading to the conclusions that pUL83/ pp65 interferes with IRF3-or NF-kB-mediated gene induction (Browne & Shenk, 2003;Abate et al, 2004). Moreover, the HCMV IE2 protein pp86 was identified as blocking IFN-b gene induction by inhibiting NF-kB DNA binding (Taylor & Bresnahan, 2006a).…”
Section: Introductionmentioning
confidence: 99%
“…We conclude that an essential component of the inhibitory supernatant generated by RICK expression plus HCMV infection is IFN-␤. It has been demonstrated clearly that HCMV can interfere with the viral-induced interferon synthesis (54,55,56). Indeed, the interferon response to UVinactivated HCMV infection is robust, whereas during the course of active HCMV replication, this response is largely suppressed (55,56).…”
Section: Ifn-␤ Is An Essential Part Of the Hcmv Inhibitionmentioning
confidence: 99%
“…It has been demonstrated clearly that HCMV can interfere with the viral-induced interferon synthesis (54,55,56). Indeed, the interferon response to UVinactivated HCMV infection is robust, whereas during the course of active HCMV replication, this response is largely suppressed (55,56). To test whether RICK is able to override these mechanisms of HCMV interferon suppression, we analyzed IFN-␤ induction in the presence of very high m.o.i.…”
Section: Ifn-␤ Is An Essential Part Of the Hcmv Inhibitionmentioning
confidence: 99%
“…Although a viral function in downregulating NF-κB signaling at the early stage of infection has been found, it is believed that the The mechanism by which pp65 inhibits the production of IFNs is controversial. One study demonstrated that pp65 inhibits IRF1 and NF-κB activity (23), while another study suggested that pp65 inhibits IRF3 activation (24). It is likely that tegument pp65 rapidly moves to the nucleus after it is delivered to infected cells and suppresses excessive antiviral cellular gene expression at very early times after infection.…”
Section: Hcmv Functions That Inhibit Nf-κb Signalingmentioning
confidence: 99%